Regulation of neural stem cell proliferation and differentiation by apoptosis-relevant factors - Santos, Daniela Vanessa Moutinho dos, 1984- (2012)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2012